Pengembangan Modul Elektronik (E-Modul) Berbasis Interaktif pada Materi Koperasi di Kelas XI SMA - Rizkita Kuscahyani; Annisya Annisya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The objective of this research is to create interactive e-module learning media. The goal is to help children in class XI-10 SMAN 8 Malang to better understand cooperative material. This research is a type of research and development (R&D). This research uses the ADDIE development model which consists of five steps consisting of analysis, design, development, implementation and evaluation. This research was carried out at SMAN 8 Malang with a student of class XI-10 of 30 students. Based on the results of material validation by material expert validators, the results showed 88.72% in the very feasible category, the results of media validation by media expert validators showed results of 83.33% in the very feasible category, and the results of student responses showed an average result of 88.46. % in the very feasible category. The average pre-test score was 41, while the average post-test score was 88.17. The findings of this research indicate that there is a difference between learning outcomes for cooperative material before and after using the interactive e-module for cooperative material. So, it can be said that the use of interactive e-modules is very feasible to apply in learning cooperative material in economics subjects in high school.